2017
DOI: 10.17507/tpls.0711.13
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Big-Five Personality Traits, English Language Proficiency Scores on IELTS, and Academic Success of Iranian Foreign Students

Abstract: Abstract-There is a potential to supply personality as a psychological factor in terms of the Big-Five Model including Extraversion, Agreeableness, Consciousness, Openness to Experience, and Neuroticism. This study was an attempt to examine the relationship between Big-Five personality traits, English language proficiency scores on IELTS, and academic success of Iranian foreign students. The participants of the study included 202 Iranian students (126 males and 76 females) who studied at English speaking unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Seyed Erfani and Mardan (2017) conducted a study on the relationship among Big Five personality traits, English language proficiency scores and academic success of Iranian students. For this purpose, they selected 202 Iranian students in foreign countries studying language-related courses.…”
Section: Introductionmentioning
confidence: 99%
“…Seyed Erfani and Mardan (2017) conducted a study on the relationship among Big Five personality traits, English language proficiency scores and academic success of Iranian students. For this purpose, they selected 202 Iranian students in foreign countries studying language-related courses.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Molaei (2016) found that the conscientiousness is very influential on the effectiveness of the ELTIS (English Language Teaching Institute) program. Likewise, Erfani and Mardan (2017) confirmed that conscientiousness is related to English language proficiency scores on IELTS, and academic success of Iranian foreign students. Dinius (2013) found that conscientiousness influences students' perceptions of English as a second/foreign language (ESL / EFL) programs.…”
Section: Discussionmentioning
confidence: 54%
“…Research has suggested that neuroticism was related to L2 learning (Lee, 2001), mostly in a negative way Zhang, 2013). For example, as proposed in Erfani and Mardan (2017)'s study, among the five personality traits in the Big Five model, neuroticism was the only personality trait that was negatively correlated with both language proficiency and academic success in a sample of Iranian students who studied at different English-speaking universities around the world. However, some research indicated that the relationship between neuroticism and L2 achievement was nonsignificant (Ghapanchi et al, 2011;.…”
Section: Conscientiousnessmentioning
confidence: 90%